2015
DOI: 10.1111/ced.12625
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of orbital arteries with colour Doppler ultrasonography in patients with psoriasis

Abstract: The haemodynamics of the orbit might be affected in patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
12
2
Order By: Relevance
“…Choroidal thickness, PASI score and disease duration were not correlated 22 . Akkurt et al reported that thickness and duration were correlated in psoriasis patients 15 . In our study, no correlation was reported between choroidal thickness and the duration of the disease.…”
Section: Discussioncontrasting
confidence: 65%
“…Choroidal thickness, PASI score and disease duration were not correlated 22 . Akkurt et al reported that thickness and duration were correlated in psoriasis patients 15 . In our study, no correlation was reported between choroidal thickness and the duration of the disease.…”
Section: Discussioncontrasting
confidence: 65%
“…The ophthalmic artery (OA) was identified immediately downstream from its crossing with the optic nerve. 9 The acoustic output of the ultrasound systems was adjusted to the requirements of the orbit ultrasonography according to the ALARA (‘as low as reasonably achievable’) principle to prevent harming the lens and retina. 13…”
Section: Methodsmentioning
confidence: 99%
“…The same observer (GRA) assessed the results of the OCDUS examinations, in accordance with previously published documents, 9,11 which were performed using a Xario Diagnostic Ultrasound System (SSA-660A, software version 4.0; Toshiba Medical Systems, Tochigi, Japan) with a linear 7.5-MHz transducer, with patients lying in the supine position with their head at a 30-degree angle. A layer of acoustic gel was applied to the closed eyelids, after which the transducer was placed on the upper eyelid, with the examiner's hand resting on the orbital margin to minimise pressure on the globe.…”
Section: Orbital Duplex Ultrasound Examinationmentioning
confidence: 99%
“…Eye involvement may also be seen in psoriasis, in which a physiopathological process similar to LP in terms of chronic inflammation is observed [8]. Especially inflammatory ocular changes and ocular surface diseases have been reported to occur in psoriasis [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the posterior segment structures may also be affected in diseases with a chronic inflammatory course, and evaluations should include the posterior segment structures of the eye [12]. Current studies have demonstrated that psoriasis may affect the posterior segment structures of the eye [8, 13]. To our knowledge, no study has evaluated the posterior structures of the eye in LP.…”
Section: Introductionmentioning
confidence: 99%